2012
DOI: 10.1016/j.hoc.2012.07.007
|View full text |Cite
|
Sign up to set email alerts
|

Myeloproliferative Neoplasm Animal Models

Abstract: Synopsis Myeloproliferative neoplasm (MPN) animal models accurately re-capitulate human disease in mice and have been an important tool for the study of MPN biology and therapy. Transplantation of BCR-ABL transduced bone marrow cells into irradiated syngeneic mice established the field of MPN animal modeling and the retroviral bone marrow transplantation (BMT) assay has been used extensively since. Genetically engineered MPN animal models have enabled detailed characterization of the effects of specific MPN as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
29
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 89 publications
4
29
0
Order By: Relevance
“…5,42,43 Although we noted a striking heterogeneity in the burden of JAK2-V617F in circulating HSPC, in agreement with a previous study of three PMF patients, 14 we confirmed a major contribution of JAK2-V617F + CD133 + cells in the engrafted animals. Thus our results are consistent with earlier studies suggesting that JAK2-V617F in the context of PMF does not hinder selfrenewal or proliferation of immunodeficient repopulating cells, 15,16 which contrasts with studies of polycythemia vera and chronic myeloid leukemia, in which Scid-repopulating cells expressing the "driver" mutations, JAK2-V617F and BCR/ABL, respectively, are detected at relatively low PMF neoplastic stem cells haematologica | 2015; 100(6) 777 16,26,44 To determine whether or not these differences reflect the target cell of mutations within the stem cell hierarchy and/or the interplay with secondary mutations will require much larger cohorts of patients.…”
supporting
confidence: 92%
See 1 more Smart Citation
“…5,42,43 Although we noted a striking heterogeneity in the burden of JAK2-V617F in circulating HSPC, in agreement with a previous study of three PMF patients, 14 we confirmed a major contribution of JAK2-V617F + CD133 + cells in the engrafted animals. Thus our results are consistent with earlier studies suggesting that JAK2-V617F in the context of PMF does not hinder selfrenewal or proliferation of immunodeficient repopulating cells, 15,16 which contrasts with studies of polycythemia vera and chronic myeloid leukemia, in which Scid-repopulating cells expressing the "driver" mutations, JAK2-V617F and BCR/ABL, respectively, are detected at relatively low PMF neoplastic stem cells haematologica | 2015; 100(6) 777 16,26,44 To determine whether or not these differences reflect the target cell of mutations within the stem cell hierarchy and/or the interplay with secondary mutations will require much larger cohorts of patients.…”
supporting
confidence: 92%
“…[2][3][4] Transgenic and knock-in mice expressing mutant JAK2 have provided compelling evidence that mutated JAK2 (typically JAK2-V617F) is a driver in this major subset of myeloproliferative neoplasms, however these mice are poor models for PMF. 5 PMF characteristics such as megakaryocyte proliferation and fibrosis have been recapitulated in mice expressing thrombopoietin, 6 the NF-E2 transcription factor, 7 vascular endothelial growth factor 8 or reduced levels of GATA1, 9 suggesting that abnormal erythroid/megakaryocyte development and/or abnormal release of cytokines may be a key factor in the disease. Although it has been postulated that aberrant interactions between the neoplastic cells and the BM microenvironment contribute to the distinct characteristics of PMF, 10 the underlying modifying mutation(s) in the context of the human neoplastic stem cell clone remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…24,[53][54][55] Accordingly, Dnm2 fl/fl Pf4-Cre mice had normal erythrocyte counts and volumes, and granulocyte and monocyte counts were increased only by 30%, whereas these parameters are severely altered in JAK2-V617F knockin mouse models. [56][57][58][59][60] DNM2 deletion in HSPCs is expected to severely alter erythropoiesis, because ubiquitous Dnm2 deletion is lethal in mice before embryonic day 8.5, 8 a stage in which first erythrocytes circulate and the heterozygous DNM2 loss-of-function mutation V235G induced by chemical mutagenesis is associated with iron deficiency anemia due to impaired transferrin uptake in mice. 61 Thus, abnormal Dnm2-null MKs and/or platelets are responsible for the severe bone marrow homeostasis defects observed in Dnm2 fl/fl Pf4-Cre mice, including HSPC expansion and MF.…”
Section: Discussionmentioning
confidence: 99%
“…Expression of WT and mutant Jak2 (Jak2 V617F ) mRNA was analyzed by reverse transcription polymerase chain reaction (RT-PCR) using allele-specific primers as described. 27 Mutant Jak2 transcripts were detected only in PB samples from PV and Picalm-deficient PV mice. RT-PCR for the housekeeping genes b-actin and Hprt was also performed.…”
Section: V617fmentioning
confidence: 95%